How COVID-19 clarified my role as chair - Mark Urtel (Academic Chairpersons Conference Proceedings, 2023)
Presenter and participants will reflect on and share their academic chair experiences and subsequent yet significant leadership alterations due directly to COVID-19. These transformations may be long- or short-term but are exclusive to being a department chair.
Keywords: COVID-19; Academic Chair; Transformation; Leadership